2004
DOI: 10.1007/bf02872382
|View full text |Cite
|
Sign up to set email alerts
|

Circadian periodicity of plasma lipid peroxides and anti-oxidant enzymes in pulmonary tuberculosis

Abstract: The circadian periodicity of plasma lipid peroxide levels and activities of superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx) were studied in 50 clinically, bactedologically and radiologically proven fresh cases of pulmonary tuberculosis (age: 21-45 years) and 60 agematched healthy volunteers with diurnal activity from 06:00 to about 22:00 and nocturnal rest. A marked circadian variation in plasma lipid peroxide level was recorded in healthy subjects and pulmonary tuberculosis patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 8 publications
(7 reference statements)
1
15
0
Order By: Relevance
“…Since FR were accused as causal factors in a large number of diseases, these were sometimes referred as ''Free Radical Diseases''. Some of the important diseases and health issues in this category are cancer [61][62][63][64][65][66][67], cardiovascular diseases [68][69][70][71][72][73], atherosclerosis [74][75][76][77][78][79][80][81], neurological disorders [82][83][84][85][86], renal disorders [87][88][89][90], liver disorders [91][92][93], hypertension [50,94,95], rheumatoid arthritis [96,97], adult respiratory distress syndrome, auto-immune deficiency diseases [98,99], inflammation, degenerative disorders associated with aging [100][101][102][103], diabetes mellitus [104][105]…”
Section: Reactive Oxygen Species and Reactive Nitrogen Species Transimentioning
confidence: 99%
“…Since FR were accused as causal factors in a large number of diseases, these were sometimes referred as ''Free Radical Diseases''. Some of the important diseases and health issues in this category are cancer [61][62][63][64][65][66][67], cardiovascular diseases [68][69][70][71][72][73], atherosclerosis [74][75][76][77][78][79][80][81], neurological disorders [82][83][84][85][86], renal disorders [87][88][89][90], liver disorders [91][92][93], hypertension [50,94,95], rheumatoid arthritis [96,97], adult respiratory distress syndrome, auto-immune deficiency diseases [98,99], inflammation, degenerative disorders associated with aging [100][101][102][103], diabetes mellitus [104][105]…”
Section: Reactive Oxygen Species and Reactive Nitrogen Species Transimentioning
confidence: 99%
“…Several studies reported that there is a day and night fluctuation of oxidative stress parameters in animals and in humans (Singh et al, 2004;Subash and Subramanian, 2007;Chakravarty and Rizvi, 2011;Xu et al, 2012). Herein, simvastatin treatment preserves T-SH level compared to basal levels.…”
Section: Discussionmentioning
confidence: 85%
“…The suprachiasmatic nucleus drives the daily regulation of biological signals. Consequently, a marked oscillations of organ functions, biochemical pathways and other biological processes were observed during 24 h (Singh et al, 2004;Subash and Subramanian, 2007). So that understanding functions of biological clock and identification of modalities to manipulate this system enable us to establish chronotherapy (Biswas et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1. The process parameters affecting the characteristics of turned parts are: cutting tool parameters, workpiece properties, cutting phenomena and cutting parameters [6]. Cutting tests were carried out on a CNC SOMAB model 500 lathe machine (24kW power) under dry cutting conditions.…”
Section: Turning Process Parametersmentioning
confidence: 99%